Latent profile analysis of health and fatigue recovery among shift work nurses and differential associations with participation in a shift work improvement pilot project: a descriptive cross-sectional study - Eunhee Jung; Eunhye Kim; Suryang Seo; Sunyoung Lee; Sora An; Hyejin Kim; Ye Seul Kim; Youjin Kim; Mijeong Park; Hyoun-Joong Kong; Saram Lee; Yeong Joo Hong; et al. (Journal of Korean Academy of Nursing, 2026)
Purpose: This study aimed to identify latent profiles of shift-work nurses according to perceived health, fatigue, and recovery levels and to examine differences across profiles in work-related outcomes, including sleep quality, work-life balance, job satisfaction, and turnover intention. It also examined whether patterns associated with participation in a shift-work improvement pilot project differed by latent profile.Methods: This descriptive cross-sectional study included 120 shift-work nurses working in pediatric wards at a tertiary hospital in South Korea. Data were collected from January 14 to 24, 2025. Latent profile analysis was performed using the 36-Item Short Form Health Survey and the Occupational Fatigue Exhaustion Recovery Scale. Differences in outcomes by latent profile membership and pilot-project participation status at the time of data collection were examined using two-way analysis of covariance, with age included as a covariate.Results: Three latent profiles were identified: Healthy-Recovery (20.8%), Moderate (41.7%), and Burnout-Vulnerable (37.5%). Significant differences among profiles were observed in sleep quality (F=37.37, p